Influence of Self-Efficacy, Individual Factors, and Motivation on Health Workers’ Patient Safety Performance through Competence-Based Human Resource Management: A Cross-Sectional Study - Faizah, Ana; Sulastri, Endang; Ruhdiyat, Agung (Chakra Brahmanda Lentera Institute, 2026)
Background: Although self-efficacy, motivation, and individual characteristics have been associated with health workers’ performance, evidence regarding the mediating role of Competence-Based Human Resource Management (CB-HRM) in patient safety implementation remains limited. This study examined the direct and indirect relationships among self-efficacy, individual factors, motivation, CB-HRM, and hospital health workers’ performance in patient safety implementation. Methods: This analytical cross-sectional survey included 98 hospital health workers at Awal Bros Hospital, Batam, Indonesia, selected using proportional random sampling. The study used a 36-item questionnaire with a five-point Likert response scale. The measurement and structural models were estimated using the path-weighting Partial Least Squares approach. Statistical inference used 5,000 nonparametric bootstrap resamples with percentile 95% confidence intervals. Reliability, convergent validity, discriminant validity, collinearity, effect sizes (f²), explained variance (R²), Q², and the Standardized Root Mean Square Residual (SRMR) were evaluated.. Results: The model explained 75.1% of the variance in CB-HRM and 80.8% of the variance in health workers’ performance. Self-efficacy (β=0.174, p=0.048), individual factors (β=0.338, p<0.001), and CB-HRM (β=0.369, p<0.001) had significant positive direct associations with performance, whereas motivation had no significant direct association (β=0.098, p=0.484). Individual factors (β=0.417, p<0.001) and motivation (β=0.396, p<0.001) were significantly associated with CB-HRM, while self-efficacy was not (β=0.109, p=0.151). CB-HRM mediated the associations of individual factors (β=0.154, p=0.007) and motivation (β=0.146, p=0.007) with performance, but did not mediate the self-efficacy association (β=0.040, p=0.145). Internal consistency was acceptable, although four HTMT ratios exceeded 0.90 and the SRMR was 0.113, indicating construct overlap and imperfect global fit. Conclusion: Seven of the ten hypotheses were supported. CB-HRM functioned as an important organizational pathway linking individual factors and motivation with patient safety performance, while self-efficacy operated mainly through a direct pathway. Hospitals should combine psychological empowerment with competency-based recruitment, placement, training, appraisal, and career development. The findings should be confirmed in larger multicenter studies using objective patient safety outcomes.